Determination of the moisture sorption behavior of osmotically dehydrated mackerel fillets by means of binary and ternary solutions - Agustinelli, Silvina Paola (2013)
In this study, the moisture sorption isotherm of osmotically dehydrated mackerel fillets (Scomber japonicus) was experimentally determined. The fillets were osmotically dehydrated with solutions of salt (NaCl) (120 and 180 g per liter of solution) or in combination with sugar (350 to 700 g per liter of solution). The sorption isotherms were determined using the static gravimetric methodology with six salts for the water activity range of 0.33–0.98 at 5 ℃ and 25 ℃. All the sorption curves were found to be type III. Temperature and the final tissue salt content had significant (p < 0.05) effects on the sorption isotherms. A regression program was used to fit the Halsey, Oswin and Smith moisture sorption isotherm models. Oswin equation gave the best fit for the whole range of water activity and temperatures. The Smith equation only presented valuable results for the mackerel fillets samples with the higher salt content.